(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Fires are a significant issue in homes, workplaces, and factories, among other places. It is hazardous and requires a high level of security and supervision in order to prevent loss of the life or property. Installing a fire alarm systems in susceptible places is one of preventative steps to avert the risk. It can detect heat in a particular environment, raise an alert, turn off the building’s mains, and even spray water to lessen the severity of the fire. This paper discusses the introduction of fire alarm systems, the advantages and challenges of a fire alarm system, as well as the different detectors that are utilized in a fire alarm system. This paper is beneficial to individuals who need knowledge about fire alarm systems. Fire alarm systems may be changed in the future by incorporating new technologies such as the Internet of Things, Machine learning and additional modules such as GSM.